ANALISIS FAKTOR PENGARUH PEMILIHAN METODE AKUNTANSI PERSEDIAAN PERUSAHAAN MANUFAKTUR DI BEI (Students' Journal of Accounting and Banking, 2012)
The objective of this study is to prove factors the affect of choice accounting inventory method. The independent variables are Managerial Ownership, Inventories Variability, Company Size, Leverage, and Capital Intensity. The dependent variable is Inventory Method, that is measured by FIFO method and average method.Objects in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) for years 2006 through 2010. Samples obtained as many as 60 companies per year. So, in this study to 300 samples consisting of 75 companies using the FIFO method and the 225 companies using the average method. Analysis tools used in this study is logistic regression with a significance level of 5% (α = 5% = 0.05)These results indicate that the Managerial Ownership, Company Size, and Leverage significant influence on the selection and inventory accounting method. Meanwhile, Variability and Intensity of Capital Stock that is not insignificant effect on the selection method of inventory accounting.Keywords: Managerial Ownership, Inventories Variability, Company Size, Leverage, Capital Intensity, and Inventory Accounting Methods.